Face recognition under adverse viewing conditions: implications for eyewitness testimony - Or, Charles C.-F. (2024)
Eyewitness testimony forms an important component in deciding whether a case can be prosecuted. Yet, many criminal perpetrators deliberately conceal their faces with disguises or under dim lighting, undermining eyewitness accuracy. This article reviews recent studies to characterize the factors that impair face recognition performance, specifically, various forms of face disguise (e.g., face masks, sunglasses) and different lighting conditions. Research shows that identification accuracy, alongside eyewitness confidence and decision bias, all affect the reliability of eyewitness accounts. A consistent finding across studies is that face-identification accuracy can be improved by matching the viewing conditions during the police lineup with those during the crime (e.g., showing masked faces during the lineup should the perpetrator be masked). Current face recognition research provides specific recommendations for optimizing the procedures in eyewitness testimony.